Gamification - A New Superpower to Enhance the Effectiveness of Educational Supervision in the Digital Age - Zaenuri Zaenuri; Dedi Yansyah (Global Education Journal, 2025)
Educational supervision in the digital era faces challenges related to teacher motivation, active engagement, and feedback effectiveness in professional development processes. This research aims to identify effective gamification models, describe their implementation, and analyze their impact on motivation, engagement, and effectiveness of educational supervision in the digital era. The study employed a qualitative approach with a case study design conducted at SDIT Insantama Rangkasbitung. Research participants consisted of school supervisors, principals, and teachers selected through purposive sampling. Data collection was carried out through in-depth interviews, participatory observation, and document analysis. Data analysis utilized thematic analysis techniques with NVivo software assistance. The findings reveal that an effective gamification model integrates a hierarchy of elements including progress bars, point systems, badges, and leaderboards with priority on feedback and follow-up aspects. Implementation was conducted through four systematic stages: Quest log in planning, Live feedback in observation, Debriefing challenge in feedback, and Action Points with a leveling system in follow-up. Significant impacts were identified in increasing teacher motivation through achievement visualization, enhancing active engagement with accelerated response and task completion, and improving supervision effectiveness measured from process dimensions, teaching quality output, to student learning outcomes. This research provides practical contributions in the form of an adaptive gamification supervision model that accommodates technological infrastructure limitations and can be replicated by schools with similar conditions.